Chronic myeloproliferative neoplasms and risk of osteoporotic fractures; a nationwide population‐based cohort study. (30th September 2013) - Farmer, Sarah; Horváth‐Puhó, Erzsébet; Vestergaard, Hanne; Hermann, Anne Pernille; Frederiksen, Henrik
Summary Patients with systemic mastocytosis have an increased risk of osteoporosis, however, the risk of osteoporotic fractures among the classic chronic myeloproliferative neoplasms (CMPN), including essential thrombocythaemia (ET), polycythaemia vera (PV) and chronic myeloid leukaemia (CML), is unknown. We conducted a population‐based cohort study to determine the risk of osteoporotic fractures among three cohorts of patients with newly diagnosed ET, PV, and CML. Patients were identified in medical registers including all Danish hospitals during 1980–2010 and were followed until first osteoporotic fracture. Fracture risk was compared to cohorts from the general population matched on age, sex and calendar year. We followed 7595 CMPN patients and 338 974 comparison cohort members. We found that the risk of femoral fracture after 5 years was consistently higher than the general population, being 3·01% (95% confidence interval (CI): 2·20–4·10), 4·74% (95%CI: 4·06–5·52) and 4·64% (95%CI: 3·29–6·53) among ET, PV, and CML patients respectively. Adjusted hazard ratio for femoral fracture was increased 1·19‐fold (95% CI: 0·94–1·51) for ET patients, 1·82‐fold (95% CI: 1·62–2·04) for PV patients, and 2·67‐fold (95% CI: 1·97–3·62) for CML patients. We conclude that CMPN patients are at higher risk of osteoporotic fractures than the general population.